Violence and the Irony of Modern Humanity in Don Baker’s Formal Application - Salsabila Zahrah Hariyana; Cynara Salma Nariswari; Samsul Ma’arif (Transpublika Publisher, 2026)
The twentieth century witnessed an unprecedented normalization of violence, as global conflicts, technological advancements in warfare, and bureaucratic systems of destruction reshaped the way societies understood cruelty and moral responsibility. This study analyzes Don Baker’s poem Formal Application as a literary critique of modern humanity and the normalization of violence in the twentieth century. Written in the historical context of World War II, the poem employs irony, symbolism, and vivid imagery to challenge the concept of “Modern Man” as a figure of progress and rationality. Using a qualitative descriptive method and close textual analysis, this study examines the poem’s narrative progression, poetic form, and use of historical allusions to reveal how violence is gradually learned, justified, and disguised through euphemistic language. The findings indicate that Baker deliberately contrasts bureaucratic civility with acts of cruelty to expose moral detachment and the erosion of empathy. Furthermore, the betrayal and killing of birds symbolize humanity’s destructive relationship with both nature and other human beings. The poem’s allusions to World War II, including references to technological warfare and ideological slogans, reinforce its condemnation of modern civilization’s ethical decline. This study concludes that Formal Application not only reflects the brutality of its historical moment but also offers a broader warning about the dangers of normalizing violence in everyday life. The findings contribute to literary studies on war poetry by highlighting the intersection of personal action, institutional violence, and moral responsibility in modern society.